Clinicopathologic features and risk factors for hepatocellular carcinoma: Results from a single center in southern Turkey - Birol ÖZER; Ender SERİN; Uğur YILMAZ; Yüksel GÜMÜRDÜLÜ; Özlem SAYGILI; Fazilet KAYASELÇUK; Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-